Pakistan : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper evaluates Pakistan's First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and a Request for Waiver and Modification of Performance Criteria. Developments in October 2001-January 2002 indicate satisfactory progress towards the program's macroeconomic objectives, although growth prospects had to be scaled down and tax revenue was lower than targeted. All but two quantitative and structural performance criteria for end-December 2001 were met. The authorities are taking corrective measures that should deliver the revised macroeconomic targets for 2001/02 provided regional tensions ease in the near future.